Evaluating the profitability of trading strategies based on technical analysis - Dutt, Andrew; Quang, Tran Van; Metrah, Samy; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2020)
The aim of this thesis is to serve as a basic guide that will help people without any prior knowledge understand technical analysis and the stock market and then to demonstrate that the information in this thesis can be used to create a functional trading strategy, which will subsequently be back-tested on historical stock market information to evaluate its profitability. The theoretical part of this thesis consists of two main chapters, which are the stock market and technical analysis, and aims to provide a basic, but good understanding of both of these topics. In the practical part, the information from the previous chapters is used to create three trading strategies that are then back-tested on three timelines, using historical stock market data of 24 different stocks and indexes, to assess their profitability and possibilites for improvement. The results of the trading strategies proved to be quite mixed, but the long positions proved to be profitable overall, and with a little optimization the strategies were able to beat the market.
Vedoucí práce: Van Quang Tran
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor bakal. práce]; bakalářské práce; bachelor's theses